BAGAIMANA UPAYA AUDIT, BIAYA AUDIT, DAN AUDIT TENURE MEMPENGARUHI KUALITAS AUDIT ? HOW AUDIT EFFORT, AUDIT FEE, AND AUDIT TENURE AFFECT AUDIT QUALITY? - Supriyanto, Supriyanto; Cesilia, Julianti (Universitas Riau, 2023)
This research aims to find how audit effort, audit fee, and audit tenure affect audit quality. The measurement of audit quality using modified audit opinion and absolute accruals discretionary. The object of this research is non-financial companies listed in Indonesia Stock Exchange (IDX) for 2017-2021. This research used purposive sampling in data collection and the data analysis using logistic regression and panel data regression. The result shows that audit effort, audit fee, and audit tenure have no significant effect on the issuance of modified audit opinion. This study also found a significant effect between audit effort and audit tenure on the quality of audited financial statements, while audit fees have no significant effect.